2021
DOI: 10.1007/s40279-021-01473-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Single Bout of Continuous Aerobic Exercise on Glucose, Insulin and Glucagon Concentrations Compared to Resting Conditions in Healthy Adults: A Systematic Review, Meta-Analysis and Meta-Regression

Abstract: Background Elevated glucose and insulin levels are major risk factors in the development of cardiometabolic disease. Aerobic exercise is widely recommended to improve glycaemic control, yet its acute effect on glycaemia and glucoregulatory hormones has not been systematically reviewed and analysed in healthy adults. Objective To determine the effect of a single bout of continuous aerobic exercise on circulating glucose, insulin, and glucagon concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Though overall insulin responses to the OGTT were lowest for EX, there were no significant effects on insulin iAUC or differences between timepoints compared to the other three trials. We found this surprising, as several studies have reported improvements in insulin responses to aerobic exercise [ 35 , 36 ]. Our results for EX may be explained most clearly by the fact that the exercise was performed 12–14 h prior to the OGTT, potentially diminishing exercise’s insulin sensitizing effects.…”
Section: Discussionmentioning
confidence: 65%
“…Though overall insulin responses to the OGTT were lowest for EX, there were no significant effects on insulin iAUC or differences between timepoints compared to the other three trials. We found this surprising, as several studies have reported improvements in insulin responses to aerobic exercise [ 35 , 36 ]. Our results for EX may be explained most clearly by the fact that the exercise was performed 12–14 h prior to the OGTT, potentially diminishing exercise’s insulin sensitizing effects.…”
Section: Discussionmentioning
confidence: 65%
“…Though overall insulin responses to the OGTT were lowest for EX, there were no signi cant effects on insulin iAUC or differences between timepoints compared to the other three trials. We found this surprising, as several studies have reported improvements in insulin responses to aerobic exercise 34,35 . Our results for EX may be explained most clearly by the fact that the exercise was performed 12-14 hours prior to the OGTT, potentially diminishing exercise's insulin sensitizing effects.…”
Section: Glucose/insulinmentioning
confidence: 62%
“…12 Acute exercise can decrease glucose and insulin concentrations in postprandial states in healthy adults, suggesting a potential role for acute exercise in improving the cardiometabolic health. 13 However, currently, there is inconsistent evidence regarding the optimal intensity, type, and duration of exercise necessary to reduce the markers of glycemia and insulinemia. Therefore, it is important to explore the influence of major exercise modalities on PPG and PPI changes.…”
Section: Introductionmentioning
confidence: 99%